Current Status and Challenges Associated with CNS-Targeted Gene Delivery across the BBB - Seigo Kimura; Hideyoshi Harashima (MDPI AG, 2020)
The era of the aging society has arrived, and this is accompanied by an increase in the absolute numbers of patients with neurological disorders, such as Alzheimer's disease (AD) and Parkinson's disease (PD). Such neurological disorders are serious costly diseases that have a significant impact on society, both globally and socially. Gene therapy has great promise for the treatment of neurological disorders, but only a few gene therapy drugs are currently available. Delivery to the brain is the biggest hurdle in developing new drugs for the central nervous system (CNS) diseases and this is especially true in the case of gene delivery. Nanotechnologies such as viral and non-viral vectors allow efficient brain-targeted gene delivery systems to be created. The purpose of this review is to provide a comprehensive review of the current status of the development of successful drug delivery to the CNS for the treatment of CNS-related disorders especially by gene therapy. We mainly address three aspects of this situation: (1) blood-brain barrier (BBB) functions; (2) adeno-associated viral (AAV) vectors, currently the most advanced gene delivery vector; (3) non-viral brain targeting by non-invasive methods.